ANALISYS OF AIR POLLUTER SO2, NO2, AND HC BY USING LINE SOURCE MODELING APPROACH (CASE STUDY AT JALAN MAGELANG YOGYAKARTA) - Ahmad Zaky Maulana (Widyariset, 2012)
This research discuss the issue of air pollution caused by movable emission in Jalan Magelang, Yogyakarta.The objective of this research is to estimate the weight of emission resulted from motor vehicle pollution. Tocalculate polluter concentration, this research use line source modelling. The result shows that the bigger polluterconcentration is NO2 that reach 211,342 μg/m3 in the daytime. The bigger polluter contributer are pick up/trucktype vehicles. The heaviest polluter weight is NO2 that reach 299 ton/year.